Evaluasi Kinerja Simpang Tiga Tak Bersinyal Jl. Muharto - Jl. Mayjen Sungkono – Jl. Raya Ki Ageng Gribig Kota Malang - Hariyanto; Aji Suraji; Mohamad Cakrawala (Program Studi Teknik Sipil Fakultas Teknik Universitas Lancang Kuning, 2022)
The unsignal intersection is the most common type of intersection found in urban areas, one of which is the unsignalized three-way intersection Muharto St. – Mayjen Sungkono St. – Raya Ki Ageng Gribig St, Malang City. Transportation problems that often occur include traffic jams and delays in travel time. Vehicle travel time as one of the service performance criteria at the intersection. These problems are often found in several areas in Indonesia, including at the intersection of Muharto St. – Mayjen Sungkono St. – Raya Ki Ageng Gribig St. is located in Malang city, which is the main route for large market vehicles to pass and is the road to access the center of Malang City as well as settlements and activities of the surrounding community. At this three-way unsignalized intersection, the traffic volume is large, so it can cause congestion at certain times. The purpose of this study was to determine the performance of Three-way unsignalized intersection Muharto st. – Mayjen Sungkono St. – Raya Ki Ageng Gribig St at 2021. The research method based on Indonesian Highway Capacity Manual (MKJI 1997) published by th Directoral General of Highways. The result of this of the study found that the volume of vehicles at Muharto St. 1430 (vehicle/hour) – Mayjen Sungkono St. 1740 (vehicle/hour) – Raya Ki Ageng Gribig St. 1913 (vehicle/hour). So Qtotal is 3554 (smp/hour) and capacity of 2522 (smp/hour). So it is known that the value of the degree of saturation after the installation of alternative traffic lights that the degree of saturation is Degree of Saturation Muharto St. (DS) 0,38 with queue length (QL) 74 m, degree of saturation of Mayjen Sungkono St. (DS) 0,28 with queue length (QL) 86 m, degree of saturation of Raya Ki Ageng Gribig (DS) 0,52 with queue length (QL) 187 m.